2015
DOI: 10.1088/1367-2630/17/8/085009
|View full text |Cite
|
Sign up to set email alerts
|

Co-controllability of drug-disease-gene network

Abstract: Controllability of a single network often focuses on the determination of the network's minimum dominating set, which aims to elaborate how to control the whole network with minimum driver nodes. This paper proposes a new framework, co-controllability of multiple networks, which stresses the control of one network by another network as well as the mutual control characteristics of multiple networks based on minimum dominating sets. We take a drug-disease-gene network that consists of a drug-drug network, a dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Another line of investigations focuses on co-controllability of networks, identifying the minimal set of driver nodes that control an entire network and quantifying mutual control characteristics of multiple networks as encountered in the human interactome. A study by Sun [52] considers a drug-disease-gene network that consist of gene-gene, disease-disease and drug-drug networks to investigate co-controllability among these networks, and to uncover underlying mechanisms of the drug-disease-gene network with applications to disease treatment and drug design.…”
Section: Towards the Human Disease Networkmentioning
confidence: 99%
“…Another line of investigations focuses on co-controllability of networks, identifying the minimal set of driver nodes that control an entire network and quantifying mutual control characteristics of multiple networks as encountered in the human interactome. A study by Sun [52] considers a drug-disease-gene network that consist of gene-gene, disease-disease and drug-drug networks to investigate co-controllability among these networks, and to uncover underlying mechanisms of the drug-disease-gene network with applications to disease treatment and drug design.…”
Section: Towards the Human Disease Networkmentioning
confidence: 99%
“…The important role of MD-nodes in network control is recognized both in theory (Nacher and Akutsu, 2012) and in various real-world networks (Nacher and Akutsu, 2013, Wan et al., 2002, Wuchty, 2014). In particular, the concept of MDSet has recently been adopted to analyze various biological networks, and the results showed that MD-nodes not only occupy strategic locations to control the networks but are also associated with various biological functions (Nacher and Akutsu, 2013, Nacher and Akutsu, 2016, Sun, 2015, Wakai et al., 2017, Wuchty, 2014, Zhang et al., 2016). Thus, we postulated that the composition of MD-nodes in a network represents its hidden control architecture.…”
Section: Introductionmentioning
confidence: 99%
“…The networks were analysed using a minimum dominating set (MDS) approach to identify potential driver nodes reactions 5 . The MDS approach was proposed by Nacher and Akutsu 7 and has been used to analyse many biological systems and identify proteins associated to cancer 812 . However, the flux coupling approach uses a discrete definition of coupling between reactions and does not take into account the full range of possible flux distributions that the metabolic system is able to support.…”
Section: Introductionmentioning
confidence: 99%